CGIAR Youth Strategy - Lecoutere, Els; Elias, Marlène; Markicevic, Isidora (International Livestock Research Institute, 2025)
Today’s youth cohort is the largest in history, and is steadily growing, particularly in low- and middle-income countries (LMICs). Approximately 15.9 percent of the global population— 1.3 billion individuals—is between 15 and 24 years old, corresponding to the UN’s definition of ‘youth’. Nearly 85 percent reside in lower-income countries, particularly in Asia and sub-Saharan Africa. The youth in Asia and the Pacific, together, represent more than 60 percent of the world’s youth. The population of youth is growing most rapidly in sub-Saharan Africa, which is expected to see a 65 percent increase, reaching around 400 million by 2050. This ‘youth bulge’ represents an unprecedented force for shaping the future of food, land and water systems (FLWS) in LMICs. Nearly half (44 percent) of working youth worldwide are employed in agrifood systems, compared to 38 percent of adults, with wide regional variations. In sub-Saharan Africa and South Asia, the majority of youth work in FLWS, mainly in agriculture. In Southeast Asia and Latin America, youth employment in FLWS is also high but more concentrated in off-farm work. Yet, youth face significant challenges in FLWS. Historic shifts, such as climate change; increasing pressure on land, water, and other natural resources; migration; urbanization; economic and geopolitical changes; digitalization; and more will shape the future of young women and men, and of the FLWS they inhabit. Despite the importance of FLWS for youth employment, more than one quarter of youth globally are not in employment, education or training (NEET) and rates of joblessness are 3.5 times higher for youth than for adults. In 2023, two-thirds of youth in NEET status globally were female. This phenomenon is even more pronounced in LMICs. In South Asia, for instance, 42.4 percent of young women are NEET—nearly four times the male rate. NEET is a situation that tends to last longer for young women than for young men. As FLWS transition to being more formalized, youth employment in agriculture declines, while off-farm employment gains importance—especially for young women. FLWS are key entry points to the labor market for younger youth (15–19), particularly in traditional FLWS. Yet older male youth (20–24) are more likely to move out of FLWS employment than older female youth. Education, marriage and parenthood influence NEET status differently by gender—education benefits young women but not young men in rural areas, while family responsibilities have the opposite pattern. Many young women classified as NEET may, in fact, be engaged in unpaid domestic and care work. Diverse groups of youth experience specific barriers in FLWS. Indigenous youth tend to face higher unemployment; low school completion rates; limited access to land, water, and ICTs; and low participation in policy and governance. At the same time, in South Asia, high rural out-migration to urban areas by youth results in farm labor shortages. In West and Central Africa, urbanization may potentially create new opportunities for the region’s agricultural value chains to meet nutrition and employment needs.